LEGAL CHARACTERISTICS OF DOMESTIC VIOLENCE AGAINST WOMEN AS A SOCIAL PHENOMENON - Litvinova, Iryna; Zhuda, Victoria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to study the legal basis of domestic violence against women as a social phenomenon. Research methods: the following methods were used: analysis method (processing of literary sources); dialectical (social relations in the sphere of protection of women from domestic violence are considered in their unity and interrelationship, the patterns of their development are revealed, the dynamics of the development of legislation in this sphere are taken into account). Results: the definition of the concept of domestic violence against women is provided. It has been established that psychological violence is the most common manifestation of domestic violence experienced by a woman, and is the basis for committing other types of violence - physical, economic and sexual. Based on the analysis of the types of domestic violence, various forms of aggressive behavior that the abuser can use against a woman have been identified. Discussion: domestic violence against women is one of the most dangerous forms of violence. In the family, a woman of any age is often subjected to physical, psychological, sexual and economic violence, which is preserved by traditional views. Lack of economic freedom and ignorance of the law force many women to remain in conditions where violence prevails. Violence puts a woman in a position that threatens her health, causes harm and deprives her of the opportunity to participate in family and public life on an equal basis with a man, that is why it is so important to pay attention to the effectiveness of the exercise of powers by the entities that carry out measures in the field of prevention and combating domestic violence among women in accordance with the provisions of the normative legal acts that regulate the activities of such entities.